Multi-phases of islet beta-cell function change in type 2 diabetes mellitus and its influencing factors - Cheng, Jin; Li, Jun; Xin, Yaping; Zhang, Dongming (Frontiers in Endocrinology, 2025)
AimsBased on cross-sectional and follow-up data, we aimed to explore the continuous long-term pattern of beta-cell function change in type 2 diabetes and to analyze the relevant influencing factors.Materials and methodsData from 2898 type 2 diabetic subjects were retrospectively analyzed. Islet beta-cell function was evaluated by the homeostasis model assessed index (HOMA-β). The pattern of association between HOMA-β and disease duration coverup of 50 years were explored using non-linear regression approaches. Findings were replicated in longitudinal follow-up data from multi-centers. Influencing factors of both residual HOMA-β level and HOMA-β decline rate were investigated.ResultsWe identified a model including three clear phases of HOMA-β change: an initial ascending phase over 4.2 years from diagnosis (3.34% change per year [95%CI 0.04, 6.52]), followed by a phase of exponential fall up to 20.9 years from diagnosis (-3.04% change per year [95%CI -3.78, -2.29]) and thereafter a low and plateau phase (0.17% change per year [95% CI -0.72, 1.05]). Longitudinal follow-up data verified this model. Higher BMI (OR = 1.103 [95%CI 1.047, 1.161]), UA (OR = 1.003 [95%CI 1.001, 1.005]), metabolic Syndrome (OR = 1.526 [95%CI 1.021, 2.279]) and lower HbA1c (OR = 0.695 [95%CI 0.627, 0.771]) levels were independently associated with higher residual HOMA-β level. Earlier diagnosis (Coefficient=0.0009 [95%CI 0.0002, 0.0016]) was independently associated with faster HOMA-β decline.ConclusionsBeta-cell function change in the course of type 2 diabetes was nonlinear with multi-phases. Targeting the factors that affect different phases would contribute to the protection of the disease progression.